AYURVEDIC APPROACH OF MENORRHAGIA: ASRIGDARA - Lakshmi, Vijay (International Journal of Ayurveda and Pharma Research, 2017)
Menorrhagia is a most common gynecological problem found in Prasuti tantra OPD. It is not a disease but it is symptom found in many gynecological disorders. Menorrhagia is characterized by the excessive bleeding per vaginum in amount and duration both. In Ayurvedic classics, Menorrhagia is termed as Asrigdara, means excessive discharge of blood per vaginum. Backache, pain in lower abdomen and weakness are also present in this disease. All the gynecological disorders come under the heading of Yonivyapad in Ayurvedic classics. Most of the Yonivyapad have characteristic features of menorrhagia such as Raktayoni, Rudhirkashara, Putraghni, Apraja etc. Among Ashta-artavadushti, Raktaja artava-dushti menorrhagia is also found as prominent symptom. Since, Asrigdar is mainly due to vitiation of Vata and Pitta dosha hence, the treatment should be based on the use of drugs which are having predominance of Kashaya rasa and Pitta –shamak properties. Kashaya rasa is known as best astringent and because of this property Kashaya rasa plays important role in relieving bleeding discharge due its Stambhana action. There is loss of blood, so, the drugs and diet which increases Rakta dhatu (Blood) in body are also effective. Therefore, treatment mainly based on concept of Raktastambhaka as well as Raktavardhaka.